Advances in mesenchymal stem cells therapy for tendinopathies - Xu-Feng Mao; Xi-Qian Zhang; Zhe-Yu Yao; Hai-Jiao Mao (Chinese Journal of Traumatology, 2024)
Tendinopathies are chronic diseases of an unknown etiology and associated with inflammation. Mesenchymal stem cells (MSCs) have emerged as a viable therapeutic option to combat the pathological progression of tendinopathies, not only because of their potential for multidirectional differentiation and self-renewal, but also their excellent immunomodulatory properties. The immunomodulatory effects of MSCs are increasingly being recognized as playing a crucial role in the treatment of tendinopathies, with MSCs being pivotal in regulating the inflammatory microenvironment by modulating the immune response, ultimately contributing to improved tissue repair. This review will discuss the current knowledge regarding the application of MSCs in tendinopathy treatments through the modulation of the immune response.